Gambaran Jumlah Neutrofil Darah Tepi Pasien Penyakit Paru Obstruktif Kronik (PPOK) di Ruang Rawat Inap RSUD Arifin Achmad Provinsi Riau Tahun 2017 - Qurnia Siti Hurul Aini; Adrianison Adrianison; Fridayenti Fridayenti (Jurnal Ilmu Kedokteran, 2019)
Chronic Obstructive Pulmonary Disease (COPD) is a common, preventable and treatable diesease that is characterized by progressive and persistent airflow limitation in respiratory tract and associated with an inflammatory response caused by exposure to noxious particles or gases. Several study showed that neutrophils are more activated and plays an important role in phatogenesis of COPD patients. The aim of this study is to know the description of peripheral blood neutrophil of COPD patients. This study was using descriptive retrospective design with total sampling technique. The sources of data were medical records of COPD patients in January – Desember 2017 with number of sample is 137 patients. The results of this study is COPD patients with high neutrophils were found in 94 (68,61%) patients. This study shows that COPD patients at lung wards Arifin Achmad Regional General Hospital Riau Province in 2017 obtained neutrophilia.